Oral hemangioma or vascular malformation: Different entities! - Ujwala Rohan Newadkar (Wolters Kluwer Medknow Publications, 2015)
The confusing and often misleading terminology used to define oral vascular tumescences along with the generic use of the term hemangioma has led to inappropriate grouping of a number of entities that are known to be biologically distinct. In many cases, the differential diagnosis between hemangioma and vascular malformation cannot be made on the basis of routine analysis. Hemangiomas were differentiated from vascular malformations by their clinical appearance, histopathologic features, and biologic behavior. However, the term hemangioma is still overapplied by clinicians and pathologists without regard to etiology or clinical behavior. Thus, a critical approach toward vascular tumescence represents the first step to reach a correct diagnosis, understand the disease pathogenesis, and provide better therapy. Here, a case report of arteriovenous malformation in the oral cavity is presented.